2005
DOI: 10.1016/j.chroma.2005.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatographic method for quantifying polyphenols in ciders by direct injection

Abstract: An analytical method for the quantitative determination of the principal phenolic compounds (benzoic acids, hydroxycinnamic acids, 3-phenylpropionic acids, flavanols, procyanidins, dihydrochalcones, quercetin glycosides) in ciders, which successfully employs a RP-HPLC and photodiode-array detection system without prior treatment of the sample, is described. Parameters usually examined in the method validation were evaluated. Good linearity was obtained with correlation coefficients exceeding 0.999 and the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…HPLC analysis was performed according to a previously described method (Suárez et al 2005) using a Waters system equipped with a 717 automatic injector, a column oven, two pumps (model 510), a diode array detector (model 2996) and the Empower 2 software data module. Separation of polyphenols was carried out on a reversed-phase Nucleosil 120 C 18 (250 Â 4.6 mm I.D, 3 mm) column (Teknokroma, Barcelona, Spain) at 30 1C, using a flow rate of 0.8 ml/min.…”
Section: Reversed-phase High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…HPLC analysis was performed according to a previously described method (Suárez et al 2005) using a Waters system equipped with a 717 automatic injector, a column oven, two pumps (model 510), a diode array detector (model 2996) and the Empower 2 software data module. Separation of polyphenols was carried out on a reversed-phase Nucleosil 120 C 18 (250 Â 4.6 mm I.D, 3 mm) column (Teknokroma, Barcelona, Spain) at 30 1C, using a flow rate of 0.8 ml/min.…”
Section: Reversed-phase High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…These methods usually involve a chromatographic separation using RP-LC with conventional C 18 columns and, some of them, a previous SPE step to remove or minimize interferences from sample matrix [9,10,14]. More recently, it has been reported that the determination of phenolics in ciders is done by direct injection [17] using conventional C 18 columns.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC analysis was performed according to the method validated by our group (Suárez, Palacios, Fraga, & Rodríguez, 2005). We used a Waters system equipped with a 717 automatic injector, provided with a column oven, two pumps (model 510), a diode array detector (model 2996) and Millennium software v.3.1 data module.…”
Section: Liquid Chromatographic Analysis Of Phenolic Compoundsmentioning
confidence: 99%